2012
DOI: 10.1002/cncr.27510
|View full text |Cite
|
Sign up to set email alerts
|

p38 mitogen‐activated protein kinase signaling, ERCC1 expression, and viability of lung cancer cells from never or light smoker patients

Abstract: BACKGROUND: Expression of DNA‐repair proteins and activated mitogen‐activated protein kinases (MAPKs) may differ according to smoking status. The authors investigated whether p38 MAPK activity contributed to the viability of cisplatin in lung cancer cell lines from never or light smokers and to ERCC1 mRNA expression. METHODS: Activated p38 MAPK was tested as a predictor for ERCC1 levels in 117 lung adenocarcinomas. Cell viabilities of NCI‐H1975, NCI‐H1793, NCI‐H1650, and NCI‐H1651 cell lines, derived from neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Related researches mention that AA cause activation of mitochondrial pathway via regulating B cell CLL/lymphoma 2 (BCL2) family proteins and increasing the ratio of Bax to Bcl2 which lead to cancer cell apoptosis [19,20]. Previous studies revealed that the AA-induced apoptosis of human cancer cell is mediated by the mitogen-activated protein kinase (MAPK) pathway with or without involving the activated caspases [5,6,21]. The inhibition of ERK and p38 phosphorylation in AA-treated cancer cell are also noted [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related researches mention that AA cause activation of mitochondrial pathway via regulating B cell CLL/lymphoma 2 (BCL2) family proteins and increasing the ratio of Bax to Bcl2 which lead to cancer cell apoptosis [19,20]. Previous studies revealed that the AA-induced apoptosis of human cancer cell is mediated by the mitogen-activated protein kinase (MAPK) pathway with or without involving the activated caspases [5,6,21]. The inhibition of ERK and p38 phosphorylation in AA-treated cancer cell are also noted [15].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al proposed that the resistance might be sensitized by increasing Bax/Bcl-2 mRNA ratios caused by inhibited NFκB expression and downregulating ERCC1 and thymidine phosphorylase (TP) by inhibiting the phosphorylation of ERK, p38 and PI3K/AKT pathways, which all lead to apoptosis, in human hepatoma HepG2 cells [23]. Another research also revealed the decreased ERCC1 mRNA expression by downregulation of p38 MAPK pathway [21]. Consistent with these studies, our results revealed significantly increased expression of Bax and decreased phosphorylation of ERK in AA-treated cis-NPC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…As of now, functional role of hsa-miR-1293 in cancer is very limited. According to miRWalk [21] and StarBase [33], one of the predicted targets of hsa-miR-1293 is MAPK14 (p38) which has been shown to be associated with tumor's sensitivity to cis -platinum treatment [34]. If this predicted relationship could be validated, then expression of this miRNA may be useful in prediction of patient's sensitivity to cis -platinum treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2A). In addition to E-cadh (34), alterations in other factors like p38MAPK (35), twist (36), cyclin D1 (37) and DNA repair capacity (38) are also involved in smoking related reduced survival in cancer patients. Our results reveal, for the first time, that smoking-mediated decrease in E-cadh expression plays a key role in the induction in EMT in lung cancer.…”
Section: Discussionmentioning
confidence: 99%